Relationships that work four ways to connect (and set boundaries) with colleagues, students, and parents - Saenz, Adam; Dew, Jeremy (Routledge, 2016)
Teaching is an extremely gratifying profession, but it can also be draining if you don't have fulfilling relationships and the ability to avoid toxic, negative people. This unique book, written by bestselling author and psychologist Adam Sâaenz and child/adolescent therapist Jeremy Dew, shows you how to increase job satisfaction and personal fulfilment by connecting with others. You'll learn about the relationships you can forge with students, colleagues, and parents to foster a healthy and life-changing learning environment, while also avoiding social and personal stress. In particular, you'll uncover how to: Build bridges to connect with students in a positive manner, making a difference in their lives. Interact with colleagues and parents in productive ways. Examine and evaluate your professional relationships. Build fences to protect yourself from harm or frustration and remain relationally engaged. Manage your emotions effectively, and learn how to express and direct them appropriately in the classroom. Throughout each chapter, you'll find strategies, reflection questions, and assessment tools to help you apply the book's concepts. Relationships That Work is an essential read for teachers at all grade levels who want not only to educate but also to guide, nurture, encourage, and form deep, long-lasting bonds -- Book jacket.